Temperature Variability in Titan's Upper Atmosphere: The Role of Wave Dissipation. Issue 6 (7th June 2020) - Wang, Xing; Lian, Yuan; Cui, Jun; Richardson, Mark; Wu, Zhaopeng; Li, Jing
Abstract: The Cassini spacecraft detected a surprisingly large temporal temperature variability of 60 Kin Titan's upper atmosphere during multiple flybys. Previous efforts examining such a variability focused on the role of radiative heating but were unable to explain the observations. Analytic estimates of the wave energy fluxes have suggested that wave heating might be an important process affecting the thermal structure of the upper atmosphere. However, approaches to date have been highly idealized and have not described wave propagation rigorously. Here, we implement an anelastic linearized wave model adopting the Wentzel‐Kramers‐Brillouin approximation that adequately describes wave propagation in Titan's upper atmosphere, where the observed vertical wavelengths are several times larger than the density scale height. Our results show that the wave heating and cooling rates generated by molecular diffusion of monochromatic waves are larger than those found in previous studies. The energy fluxes associated with wave dissipation can exceed that of the combined solar extreme ultraviolet (EUV) heating and HCN rotational line cooling. Compared to the wave‐free, mean‐state temperature, the wave energy fluxes associated with certain wave modes can produce a temperature variability as large as 20 K, which is larger than that driven by magnetospheric particle precipitation but still smaller than that observed. Our results suggest that wave heating and cooling are important processes that can modify the thermal structure of Titan's upper atmosphere and also suggest that additional processes such as wave breaking and molecular diffusion of a spectrum of waves should be considered in future studies. Plain Language Summary: The Cassini spacecraft detected a surprisingly large temperature variability of 60 Kin Titan's upper atmosphere. The roles of several notable heating and cooling mechanisms such as solar EUV radiation, charged particle precipitation, and HCN rotational line emission have been evaluated in previous works, but none of them can explain the observations. In this study, we construct a linearized wave model to evaluate the role of wave dissipation, which is well known to be able to affect the atmospheric thermal structure on various solar system objects. Previous estimates of the same mechanism have been highly idealized and have not described wave propagation adequately. Our model results show that the wave heating and cooling rates generated by molecular diffusion of monochromatic waves are substantially larger than those reported in previous studies. The wave‐induced temperature variability in Titan's upper atmosphere that we obtain could reach 20 K, which is larger than that driven by charged particle precipitation from the ambient plasma, but still smaller than that observed by a factor of three. It is likely that additional wave processes such as wave breaking and molecular diffusion of a spectrum of waves make further contributions to the observed temperature variability in Titan's upper atmosphere. Key Points: We construct a linearized wave model to evaluate the role of wave heating and cooling in Titan's upper atmosphere Wave heating by molecular diffusion is an important mechanism that influences the thermal structure of Titan's upper atmosphere The predicted temperature variability is likely greater than that caused by particle precipitation but still smaller than that observed